2015
DOI: 10.7567/jjap.54.06fp08
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric energy harvester operated by noncontact mechanical frequency up-conversion using shell cantilever structure

Abstract: In this study, we propose and demonstrate a piezoelectric energy harvester with a shell cantilever for mechanical frequency up-conversion to generate electric power in a low-frequency vibration environment. The proposed device is composed of a clamped semicylindrical shell cantilever as a driving beam and a piezoelectric cantilever attached to the proof mass of the shell cantilever as a generating beam. The shell cantilever bends downward when the external acceleration is over the threshold value for buckling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Acoustic and thermal were also active during the mechanical impacts. Yun et al (Han and Yun, 2014; Jang et al, 2015; Jung and Yun, 2010) implemented the FUC effect by high impulse-like accelerations without physical contact; the harvesters provided the inertia impacting force to the high-resonance oscillators through the instantaneous state transition of a shell cantilever or a bucked bridge, but the fatigue life of the structures need to be designed to a very high standard. The magnetic coupling force can also been selected to generate the impulse-like acceleration without physical contact; Rastegar and Murray (2010), Wickenheiser and Garcia (2010), and Tang et al (2012) have already demonstrated this kind of energy harvesters.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic and thermal were also active during the mechanical impacts. Yun et al (Han and Yun, 2014; Jang et al, 2015; Jung and Yun, 2010) implemented the FUC effect by high impulse-like accelerations without physical contact; the harvesters provided the inertia impacting force to the high-resonance oscillators through the instantaneous state transition of a shell cantilever or a bucked bridge, but the fatigue life of the structures need to be designed to a very high standard. The magnetic coupling force can also been selected to generate the impulse-like acceleration without physical contact; Rastegar and Murray (2010), Wickenheiser and Garcia (2010), and Tang et al (2012) have already demonstrated this kind of energy harvesters.…”
Section: Introductionmentioning
confidence: 99%
“…Either way, the low-frequency ambient vibration can be up-converted to the higher frequency vibration of the beams, which then improves harvesting efficiency. Frequency up-conversion can also be achieved without any physical impact or contact in PEH systems, for instance, through magnetic plucking [28][29][30] or using a cantilever shell structure [31]. Both of these configurations can generate an impact-like force or impulsive excitation which then increases the dominant response frequency of the cantilevers.…”
Section: Vibro-impact Systems In Energy Harvestingmentioning
confidence: 99%
“…Energy harvesting is considered as an alternative technology to overcome the issues of the current power supply source for wearable sensors [ 7 , 8 , 9 ]. An energy harvester utilizes various energy sources to generate electric power, including light [ 10 , 11 ], radio frequency [ 12 , 13 ], temperature difference [ 14 , 15 , 16 ], and mechanical energy [ 17 , 18 , 19 , 20 , 21 , 22 ]. Among them, mechanical energy is considered suitable for wearable applications because it is not influenced by environmental conditions such as weather and location.…”
Section: Introductionmentioning
confidence: 99%